In vitro and In vivo characterization of anti-biofilm activity of LpxC inhibitor alone, and in combination with different classes of antimicrobials - Tan, Jun Hou (2018)
Biofilms are multicellular bacterial communities that are formed on a surface and encased in extracellular polymeric substance (EPS) made up of eDNA, proteins and exopolysacchrides. Due to their distinct - instrinic, acquired and adaptive - antimicrobial resistance, biofilm formation is one of the main common causes of chronic infections and is becoming increasingly difficult to treat with existing antibiotics. Without anti-biofilm therapy that targets biofilm specifically, combination antimicrobial therapy remains one of the most effective strategies to eradicate biofilms.